Pengaruh Earning Per Share Dan Net Profit Margin Terhadap Harga Saham Dalam Indeks LQ45 Periode 2020-2024 - Sherin Julianti Erica Putri; Ratna Juwita (Universitas Multi Data Palembang, 2026)
This study aims to examine the effect of Earning Per Share (EPS) and Net Profit Margin (NPM) on the stock prices of companies listed in the LQ45 index during the 2020-2024 period. This study employs a quantitative approach using multiple linear regression analysis. The data used are secondary data obtained from company financial statements and official publications available on the Indonesia Stock Exchange. The sampling technique used is purposive sampling on predetermined criteria. The results show that EPS and NPM have a significant effect on stock prices. Simultaneously, all variables have a significant effect on stock prices. This study is expected to contribute to investors as a consideration in making investment decision and to academics as a reference for future researchers.